The impact of community health worker-led home delivery of antiretroviral therapy on virological suppression: a non-inferiority cluster-randomized health systems trial in Dar es Salaam, Tanzania - Geldsetzer, Pascal; Bärnighausen, Till (BMC health services research, 2017)
Home delivery of antiretroviral therapy (ART) by community health workers (CHWs) may improve ART retention by reducing the time burden and out-of-pocket expenditures to regularly attend an ART clinic. In addition, ART home delivery may shorten waiting times and improve quality of care for those in facility-based care by decongesting ART clinics. This trial aims to determine whether ART home delivery for patients who are clinically stable on ART combined with facility-based care for those who are not stable on ART is non-inferior to the standard of care (facility-based care for all ART patients) in achieving and maintaining virological suppression.